2022
DOI: 10.18549/pharmpract.2021.4.2449
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an interprofessional student-led influenza vaccination clinic for medical, nursing and pharmacy students

Abstract: Background: Students in their final years of medicine, nursing and pharmacy degrees were invited to participate in an interprofessional influenza vaccination training course and clinic. Twenty-four students (8 from each discipline) were selected to participate. After vaccination training these students administered free influenza vaccines under supervision in two student-led clinics to 546 students in health and allied health programs prior to their clinical placements. Objective: To evaluate the students' exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Through the application of HFS in this study, there was an integration of different emergency cases—potentially arising after vaccination administration—that may or may not be directly related to vaccination, such as asthma exacerbation. As an aside, other studies on vaccination training have only focused on anaphylactic reactions [ 50 , 52 , 53 ]. Students in the HFS group particularly demonstrated significantly better performance in terms of recognizing and handling emergency situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the application of HFS in this study, there was an integration of different emergency cases—potentially arising after vaccination administration—that may or may not be directly related to vaccination, such as asthma exacerbation. As an aside, other studies on vaccination training have only focused on anaphylactic reactions [ 50 , 52 , 53 ]. Students in the HFS group particularly demonstrated significantly better performance in terms of recognizing and handling emergency situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be stressed that these participants’ perception of their ability was at variance from their actual performance during the study. Their lack of confidence could be addressed by scheduling trainings at an early stage and assigning the students with a responsibility to vaccinate, such as what was demonstrated by Peter R. Caroll and colleagues when they developed a student-led vaccination clinic for the purposes of training medical, nursing, and pharmacy students [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The training was found to have a positive impact on students’ knowledge and skills. Another investigation examined the impact of inter-professional training on vaccination administration, where participants from the health disciplines of medicine, nursing and pharmacy received training and ran an immunization clinic [ 28 ]. The investigators found a significant increase in knowledge, confidence and skills regarding influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to scheduling patients in our institution’s vaccine clinic, we vaccinated 68 patients in the ED in two months using student-led patient screening and education. Past studies have shown the value of involving medical and pharmacy students in influenza vaccination initiatives, 12 , 13 , 18 but to our knowledge, studies about student-facilitated, ED-based COVID-19 vaccination programs are lacking. We found a higher vaccine acceptance rate after a brief educational intervention and that more vaccines were given when students were present.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The purpose of this quality improvement (QI) pilot study was to improve vaccine uptake among patients offered COVID-19 vaccination in the ED. While it can be difficult for the care team to have thoughtful conversations with vaccinehesitant patients due to time constraints, other resources such as students 12,13 may be available. Therefore, in this study we examine COVID-19 vaccine acceptance using medical and pharmacy students as dedicated COVID-19 vaccine screeners for ED patients.…”
Section: Introductionmentioning
confidence: 99%